Multicenter, placebo‐controlled, double‐blind, randomized study of fosnetupitant in combination with palonosetron for the prevention of chemotherapy‐induced nausea and vomiting in patients receiving highly emetogenic chemotherapy. Issue 22 (5th August 2019) - Sugawara, Shunichi; Inui, Naoki; Kanehara, Masashi; Morise, Masahiro; Yoshimori, Kozo; Kumagai, Toru; Fukui, Tomoya; Minato, Koichi; Iwashima, Akira; Takeda, Yuichiro; Kubota, Kaoru; Saeki, Toshiaki; et al.
Abstract : Background: The current randomized, double‐blind, phase 2 study assessed the efficacy and safety profile of a single intravenous administration of fosnetupitant, a neurokinin 1 receptor antagonist prodrug, for the prevention of chemotherapy‐induced nausea and vomiting in Japanese patients receiving cisplatin‐based chemotherapy. Methods: Patients scheduled to receive cisplatin (at a dose of ≥70 mg/m 2 )‐based regimens were randomly assigned to receive fosnetupitant at a dose of 81 mg or 235 mg or placebo in combination with palonosetron at a dose of 0.75 mg and dexamethasone. The primary endpoint was complete response (CR; no vomiting and no rescue medication) during the overall phase (0‐120 hours). The overall CR rate was compared between each dose of fosnetupitant and the placebo group adjusting for the stratification factors of sex and age class (age <55 years vs age ≥55 years). Safety was assessed, with special attention given to events that potentially were suggestive of infusion site reactions. Results: A total of 594 patients were randomized. Of these, 194 patients, 195 patients, and 195 patients, respectively, in the placebo and fosnetupitant 81‐mg and 235‐mg dose groups were evaluable for efficacy. The overall CR rate was 54.7% for the placebo group, 63.8% for the fosnetupitant 81‐mg dose group (adjusted difference, 9.1%; 95% CI, ‐0.4% to 18.6% [ P  = .061]), and 76.8% for the fosnetupitant 235‐mg dose group (adjusted difference, 22.0%; 97.5% CI, 11.7% to 32.3% [ P  < .001]). Safety profiles were comparable between the 3 groups. The incidence of infusion site reactions related to fosnetupitant was ≤1% in each dose group. Conclusions: Fosnetupitant at a dose of 235 mg provided superior prevention of chemotherapy‐induced nausea and vomiting among patients receiving cisplatin‐based chemotherapy compared with the control group, and with a satisfactory safety profile. Abstract : Fosnetupitant at a dose of 235 mg combined with palonosetron and dexamethasone was demonstrated to be effective in the prevention of emesis during the first 0 to 120 hours after the administration of cisplatin. The results of the current study suggest that fosnetupitant at a dose of 235 mg also may improve the percentage of patients with no nausea in the delayed phase (24 ‐ 120 hours after cisplatin administration), which is an unmet medical need of patients with cancer who are receiving chemotherapy.